The sons of Caim: the race of outcasts and disinherited in Walter Benjamin and Charles Baudelaire - Ricardo André Ferreira Martins (Acta Scientiarum. Language and Culture, 2014)
This article aims to develop a reflection essay about the philosophical and literary representation concerning the marginalized and oppressed in history, inside the works of Charles Baudelaire and Walter Benjamin. This is to ascertain and analyze how these two authors, from their respective works, allowed the proletariat gradually took the shape of an object and productive character for social and lyrical reflection, thus, in the wake of works as Flowers of Evil, the assumption of themes drawn from a tradition historically long, connected, in turn, by the recent historiographical perspective from below.